THE DOMINATION OF THE RULING CLASS OVER THE SUBORDINATING CLASS IN THE NOVEL LASKAR PELANGI BY ANDREA HIRATA : A MARXISM STUDY - Satriani, Irma; Shafariana, Shafariana; Asri, Aswati (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
Study This aims to describe the domination class ruler to subordinate class. Research data sources This is the first time the novel Laskar Pelangi was published by Andrea Hirata by Bentang Pustaka in 2005. Type study This is descriptive qualitative. The method used was to read, note, classify, and analyze. Research results show that the novel revealed a difference in class between class rulers and subordinates, which gives birth to domination. Domination between class rulers (capital owners) and class subordination (labour) is triggered by several things, like profession, environment, and pattern of life. Race labourers are exploited because of class-decisive ruler standardization in public.